Israel's National Security Law : Political Dynamics and Historical Development. - Cohen, Amichai (Taylor & Francis, 2011)
Terror attacks on western civilian targets have stimulated interest in the dilemmas faced by liberal societies when combating threats to national security. Combining the perspectives of political science and law, this book addresses that discourse, asking how democracies seek to harmonize the protection of individual liberties with the defence of state interests. The book focuses on the experience of Israel, a country whose commitment to democratic values has continuously been challenged by multiple threats to national survival. It examines the legal, legislative and institutional methods emplo.